Teeth Reconstruction Using Artificial Intelligence: Trends, Perspectives, and Prospects - Reinhard Chun Wang Chau; Khaing Myat Thu; Richard Tai Chiu Hsung; Walter Yu Hang Lam (Taylor & Francis Group, 2023)
ABSTRACTBackground Artificial intelligence (AI) applications in dental restorative procedures have significantly developed over recent years. However, there is a lack of documentation regarding the types of AI used in tooth reconstruction.Types of Studies Reviewed Studies using AI in tooth reconstruction were electronically searched over three databases PubMed, Cochrane library, and Google Scholar. The relevancy of theme tooth reconstruction was prioritized in searching. Only original research was included without the restriction of publication time or any filters.Results A total of 18 studies were included in this review: 5 reported programmable AI systems based on mathematical models such as statistical estimation, 9 studies used biogeneric tooth libraries, and 4 presented the deep learning models.Practical Implications AI has gained significant progress over the past two decades as a powerful tool for automated tooth reconstruction. However, further studies are required to compare different forms of AIs and to assess their clinical performance in the reconstruction of occlusal surfaces.